2010
DOI: 10.1521/pedi.2010.24.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Subtypes of Adolescent Antisocial Personality Disorder

Abstract: The present study examined the application of the Antisocial Personality Disorder (APD) diagnosis to adolescents and investigated the possibility of subtypes of APD adolescents. As part of a broader study of adolescent personality in clinically-referred patients, experienced clinicians provided personality data on a randomly selected patient in their care using the SWAP-II-A personality pathology instrument. Three hundred thirteen adolescents met adult DSM-IV diagnostic criteria for APD. To characterize adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Given the correlates, it is reasonable to hypothesize that this subtype may represent adolescents who are later diagnosed as having BPD. The relationships between this Q-factor and clinician-reported symptoms of BPD certainly support this hypothesis, but it should be cautioned that emotional dysregulation is an underlying feature of many psychiatric disorders (Jones and Westen, 2010;Powers and Westen, 2009;Thompson-Brenner et al, 2008).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Given the correlates, it is reasonable to hypothesize that this subtype may represent adolescents who are later diagnosed as having BPD. The relationships between this Q-factor and clinician-reported symptoms of BPD certainly support this hypothesis, but it should be cautioned that emotional dysregulation is an underlying feature of many psychiatric disorders (Jones and Westen, 2010;Powers and Westen, 2009;Thompson-Brenner et al, 2008).…”
Section: Discussionmentioning
confidence: 89%
“…DeFife et al (2010) demonstrated that clinician-report and self-report are significantly positively correlated and that clinicianreport data are highly correlated with data obtained via structured interview by an independent assessor. In addition, other studies have been published using data on which the current study is based and address separate topics, such as eating disorders and antisocial personality (Blagov and Westen, 2008;DiLallo et al, 2009;Jones and Westen, 2010;Thompson-Brenner et al, 2008).…”
Section: Samplementioning
confidence: 99%
“…Conversely, studies 6568 focused on heterogeneity within psychiatric diagnoses suggest that subtypes of multiple psychiatric disorders (eg, eating disorders, personality disorders, anxiety disorders, and mood disorders) may be associated with varying degrees of emotion dysregulation. 6568 Alternately, the relationship between emotion dysregulation and some psychological disorders may be an interactive cascade in which emotion dysregulation increases vulnerability for the development of psychiatric disorders that in turn exacerbate emotion dysregulation. In PTSD, the presence of trauma-related cues may lead to emotion dysregulation that in turn may lead to higher levels of PTSD symptoms such as avoidance and irritability.…”
Section: Discussionmentioning
confidence: 99%
“…According to the DSM-IV-TR, persons younger than 18 years cannot be given a diagnosis of APD. Results of recent research suggest that there are no clinically significant differences between adolescents and adults who meet the criteria for APD (Jones & Westen, 2010;Taylor, Elkins, Legrand, Peuschold, & Iacono, 2007). Additionally, one study found that 54% of incarcerated juveniles met the criteria for APD, 53% of whom also met the criteria for borderline personality disorder (BPD; McManus, Alessi, Grapentine, & Brickman, 1984).…”
Section: Introductionmentioning
confidence: 99%